The impact of diabetes mellitus on the course and outcome of pregnancy during a 5-year follow-up - Mitrović, Milena; Stojić, Siniša; Tešić, Dragan S.; Popović, Djordje; Rankov, Olivera; Tomić Naglić, Dragana; Novaković Paro, Jovanka; Pejin, Radoslav; Bulatović, Sanja; Todorović Veljić, Maša; Kovačev Zavišić, Branka (Vojnosanitetski pregled, 2014)
Background/Aim. Women with diabetes, especially diabetes type 1, have worse pregnancy outcomes, as well as increased incidence of spontaneous abortions, pre-eclampsia, fetal macrosomia, preterm delivery, congenital anomalies and perinatal mortality. The aim of this study was to analyze the course and outcome of pregnancy in the patients with diabetes in relation to the group of healthy women regarding preterm delivery, perinatal morbidity and mortality. Also, the aim was to compare pregnancy outcomes in the patients with pre-existing diabetes type 1 and the patients with gestational and diabetes type 2. Methods. This retrospective study included 156 diabetic women treated at the Clinic of Endocrinology, Diabetes and Metabolic Diseases and Gynecology and Obstetrics Clinic of the Clinical Center of Vojvodina from 2006 to 2010. There were 94 patients with gestational diabetes, 48 with type 1 diabetes, and 14 patients with type 2 diabetes. The control group included 106 healthy women hospitalized at the Gynecology and Obstetrics Clinic. Results. The women with type 1 diabetes presented with a statistically significantly higher incidence of cesarean section than those without diabetes, or with type 2 or gestational diabetes (p < 0.0001); the women with type 1 diabetes delivered at an earlier week of gestation (WG) in regard to women without diabetes, or with type 2 or gestational diabetes (p = 0.0017 and p = 0.02, respectively). The incidence of perinatal morbidity: hypoglycemia (p < 0.001), pathological jaundice (p = 0.0021), and other neonatal pathologies at birth (p = 0.0031), was statistically significantly higher and Apgar scores after 1 minute (p = 0.0142) and after 5 minutes (p = 0.0003) were statistically significantly lower in the patients with diabetes compared to the healthy women. The women with type 2 and gestational diabetes were statistically significantly older than those with type 1 diabetes (p = 0.001). A higher incidence of fetal macrosomia in the women with gestational and type 2 diabetes compared to those with type 1 diabetes was at the borderline of statistical significance (p = 0.07), whereas the incidence of hypoglycemia of newborn was statistically significantly higher in the patients with type 1 diabetes (p < 0.0001). Glycosylated hemoglobin (HbA1c) levels were statistically significantly higher in the diabetic women giving birth during and before the week of gestation 36 (p = 0.0087), but there were no differences in HbA1c levels in regard to fetal macrosomia (p = 0.45) and congenital abnormalities (p = 0.32). Conclusion. The results of our study show a higher incidence of perinatal fetal morbidity (hypoglycemia, jaundice, respiratory distress syndrome) in the patients with type 1, type 2 and gestation diabetes than in the healthy controls. Also, we found a higher incidence of cesarean section in the patients with type 1 diabetes than in those with type 2, gestation diabetes and healthy controls. Although delivery in the patients with type 1, type 2 and gestational diabetes was completed approximately one to two weeks earlier compared to the healthy controls there was no statistically significant difference in the incidence of preterm delivery (≤ 36th week of gestation) between the women with diabetes and healthy controls. Preterm delivery associated with poorer glycaemic control reflected through higher values of HbA1c in third trimester. Risks from adverse pregnancy outcomes may be reduced to minimum by adequate preconception counseling of diabetic patients and early diagnosis of diabetes in pregnancy, in order to achieve glycemic control during organogenesis and within pregnancy and through the teamwork of endocrinologists, gynecologists and pediatricians.